Climate variability, farmland value, and farmers' perceptions of climate change: implications for adaptation in rural Pakistan. Issue 6 (2nd November 2017) - Arshad, Muhammad; Kächele, Harald; Krupnik, Timothy J.; Amjath-Babu, T. S.; Aravindakshan, Sreejith; Abbas, Azhar; Mehmood, Yasir; Müller, Klaus
ABSTRACT: Many studies have examined the impact of climatic variability on agricultural productivity, although an understanding of these effects on farmland values and their relationship to farmers' decisions to adapt and modify their land-use practices remains nascent in developing nations. We estimated the impacts of the deviation in our study year's (2012) temperature and precipitation patterns from medium-term (1980–2011) climatic patterns on farmland values in Pakistan. This was accomplished by employing a modified form of a Ricardian regression model. We also examined farmers' perceptions of climate change during this period, as well as their perceptions of climate change impacts on farm productivity, in addition to past and anticipated farm adaptation strategies. Our results indicate that positive temperature deviation from the medium-term mean – indicative of climatic change – affects farmland values in Pakistan. Deviation in annual cumulative precipitation conversely appears to have no significant impact. Estimates of the marginal impact of temperature deviation suggested a slight but negative linear relationship with farmland values. The location of farms in areas where farmers can avail financial or extension services conversely had a positive impact on farmland values, as did the availability of irrigation facilities. Our analysis of farmers' perceptions of climate change and their consequent adaptation behavior indicated a relatively high degree of awareness of climatic variability that influenced a number of proactive and future anticipated farm adaptation strategies. Examples included increased use of irrigation and farm enterprise diversification, as well as land-use change, including shifting from agriculture into alternative land uses. National policy in Pakistan underscores the importance of maintaining a productive rural agricultural sector. Our findings consequently highlight the importance of appropriate adaptation strategies to maintain both farm productivity and farmland values in much of Pakistan. The implications of increased extension and financial services to enhance farmers' potential for climate change adaptation are discussed.